2020
DOI: 10.3390/polym12030635
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Boron and Manganese Ions from Wet-Flue Gas Desulfurization Wastewater by Hybrid Chitosan-Zirconium Sorbent

Abstract: Flue gas desulfurization (FGD) wastewater, after the alkaline precipitation and coagulation processes, often requires additional treatment in order to reduce the concentrations of boron and heavy metals below the required limits. In this study, we present an innovative and environmentally friendly method for boron and manganese removal that is based on a hybrid chitosan-zirconium hydrogel sorbent. The results from the batch adsorption experiment indicated that the uptake capacity for boron and manganese was eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Because the stability of the biosorbent, especially the bond strength between the filler and chitosan, is a significant factor for qualifying the proposed biosorbent for use in purifying water or wastewater [ 51 ], we checked the leaching of manganese ions from the Mn-biosorbent during the sorption and desorption process. The results shown in Table 4 indicated that trace amounts of manganese eluted within sorption and desorption to the solution, but the Mn concentration was far less than the legal limit of 0.5 mg/L (the limit for manganese concentration is 0.5 mg/L, both in natural water and in wastewater discarded into the environment [ 51 , 52 ]). Furthermore, we noticed that a compact form of hydrogel beads was retained after three sorption–desorption cycles (see Figure S4 in the Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the stability of the biosorbent, especially the bond strength between the filler and chitosan, is a significant factor for qualifying the proposed biosorbent for use in purifying water or wastewater [ 51 ], we checked the leaching of manganese ions from the Mn-biosorbent during the sorption and desorption process. The results shown in Table 4 indicated that trace amounts of manganese eluted within sorption and desorption to the solution, but the Mn concentration was far less than the legal limit of 0.5 mg/L (the limit for manganese concentration is 0.5 mg/L, both in natural water and in wastewater discarded into the environment [ 51 , 52 ]). Furthermore, we noticed that a compact form of hydrogel beads was retained after three sorption–desorption cycles (see Figure S4 in the Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…Russia also contributes to many topics and brings the ecotechnological perspective of space exploration [ 40 ]. Relevant papers from Indian authors were focused on wastewater treatment [ 41 , 42 ], particularly in the textile industry [ 43 ], while Poland authors explored the use of ECT for recycling carbon, heavy metal removal, and recovery of nitrogen and phosphorus from wastes [ [44] , [45] , [46] ].…”
Section: Countries’ Production Vs Specialization: a Multidimensional ...mentioning
confidence: 99%
“…In this regard, lanthanoid complexes have interesting spectroscopic properties-such as large Stokes shift, narrow emission bands, long emission lifetimes and high emission quantum yields [12]-being a good alternative as sensors for detection of cations, anions and biomolecules. In fact, the detection of metals, such as copper(II)-a relevant ion for biochemical and environmental issues [13][14][15]-can be done by different methods, including electrochemical methods, UV-vis spectroscopy, atomic absorption, inductively coupled plasma and atomic emission spectrometry (ICP-AES) [16][17][18][19]. These methods generally require costly equipment and the specific preparation of samples.…”
Section: Introductionmentioning
confidence: 99%